2011
DOI: 10.1210/jc.2010-2813
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Estimates of Insulin Sensitivity in Obese Youth along the Spectrum of Glucose Tolerance from Normal to Prediabetes to Diabetes

Abstract: In obese adolescents with normal or impaired glucose tolerance or diabetes, OGTT-derived surrogates do not offer any advantage over the simpler fasting indices, which correlate strongly with clamp insulin sensitivity. Surrogate indices of insulin sensitivity could be used in epidemiological studies but not to define insulin resistance in individual patients or research subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 38 publications
3
109
1
3
Order By: Relevance
“…Previous investigations suggested a lower degree of insulin resistance in PWS when compared to nonsyndromic obesity [24, 25]. However, in our study, either GH therapy [26] or obesity [27] could account for comparable insulin concentrations in those with PWS and obese controls. Considering the lack of hypoglycemia experienced by the children in the present study and the increase in glucose IP (see below), the lack of an increase in glucagon is normal [28].…”
Section: Discussioncontrasting
confidence: 58%
“…Previous investigations suggested a lower degree of insulin resistance in PWS when compared to nonsyndromic obesity [24, 25]. However, in our study, either GH therapy [26] or obesity [27] could account for comparable insulin concentrations in those with PWS and obese controls. Considering the lack of hypoglycemia experienced by the children in the present study and the increase in glucose IP (see below), the lack of an increase in glucagon is normal [28].…”
Section: Discussioncontrasting
confidence: 58%
“…Finally, the use of fasting insulin, or its inverse or HOMA, as surrogate estimates of insulin sensitivity, may perhaps be viewed as a limitation. However, our group has shown that these surrogate estimates correlate strongly with in vivo insulin sensitivity measured with the hyperinsulinemic-euglycemic clamp in youth with NGT, PD and diabetes [46], particularly when applied to large numbers.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Homeostatic Model Assessment V.2 (HOMA2), which is derived from fasting values, as an assessment of insulin sensitivity 21. Fasting insulin concentrations correlate well with insulin sensitivity as measured by the hyperinsulinemic clamp in adults22 and fasting-derived surrogates have been found to be robust in some paediatric studies as well 23. On the other hand, fasting values have also been deemed to be a poor measure of insulin sensitivity 20.…”
Section: Methodsmentioning
confidence: 99%